Efficacy of Resistance to Francisella Imparted by ITY/NRAMP/SLC11A1 Depends on Route of Infection - Powell, Daniel A.; Frelinger, Jeffrey A. (Frontiers in Immunology, 2017)
NRAMP (Natural Resistance Associated Macrophage Protein, encoded by the Slc11a1 gene is a membrane-associated transporter of divalent metal ions. Murine Slc11a1 has two known alleles, a functional Slc11a1Gly169, which is found in DBA2/J, NOD/LtJ, and 129p3/J and related mouse strains, and a non-functional Slc11a1Asp169, that is found in C56Bl/6J (B6) and BALB/cJ mice. B6 mice congenic for Slc11a1Gly169 (B6- Slc11a1G169) are markedly resistant to the intracellular pathogens Salmonella, Leishmania, and Mycobacterium tuberculosis. We examined the host cell response and replication of Francisella in B6- Slc11a1G169 mice. Bone marrow derived macrophages (BMDM) from either B6- Slc11a1G169 or B6 mice were both effectively invaded by Francisella Live Vaccine strain (LVS). However, at 16 hours post infection (hpi) the number of LVS bacteria recovered from B6 macrophages had increased roughly 100 fold, while in B6- Slc11a1G169 mice the number decreased 10 fold. When the mice were challenged intranasally (i.n.) B6 mice lost significant amounts ( 15%) of weight, where as B6- Slc11a1G169 mice lost no weight. Three days after infection in B6- Slc11a1G169 mice we failed to recover viable Francisella from the lungs, livers or spleens. In contrast, B6 mice had bacterial burdens approaching 1x106 CFU/organ in all three organs. To further examine the degree of resistance imparted by Slc11a1Gly169 expression, we challenged mice deficient in TLR2, TLR4, and TLR9, but expressing the functional Slc11a1 (B6- Slc11a1G169 Tlr2/4/9-/-). Surprisingly, B6- Slc11a1G169 Tlr2/4/9-/- mice had no notable weight loss. 80% of B6- Slc11a1G169 Tlr2/4/9-/- mice yielded no detectable Francisella in any organ tested. Additionally, Slc11a1G169 produced little detectable cytokine either in the lung or serum compared to B6 mice. Mice expressing Slc11a1Gly169 survived even high doses ( 80 LD50) of LVS inoculation. These data taken together serve to highlight that functional Slc11a1Gly169 can compensate the lack of TLR2/4/9. Thus Slc11a1 is a critical player in murine resistance to pulmonary Francisella infection, but not footpad infection.